Reimaging Zen in a Secular Age : Charles Taylor and Zen Buddhism in the West - Braak, André van der (Currents of Encounter, 2020)
In Reimagining Zen in a Secular Age André van der Braak offers an account of the exciting but also problematic encounter between enchanted Japanese Zen Buddhism and secular Western modernity over the past century, using Charles Taylor's magnum opus A Secular Age as an interpretative lens. As the tenuous compromises of various forms of "Zen modernism" are breaking down today, new imaginings of Zen are urgently needed that go beyond both a Romantic mystical Zen and a secular "mindfulness" Zen. As a Zen scholar-practitioner, André van der Braak shows that the Zen philosophy of the 13th century Zen master Dōgen offers much resources for new hermeneutical, embodied, non-instrumental and communal approaches to contemporary Zen theory and practice in the West.